Chemsex and Mental Health of Men Who Have Sex With Men in Germany - Bohn, Annette; Sander, Dirk; Köhler, Thorsten; Hees, Nico; Oswald, Felix; Scherbaum, Norbert; Deimel, Daniel; Schecke, Henrike (Frontiers in Psychiatry, 2020)
Background: Chemsex is defined as using substances immediately before or during sexual activities to facilitate, prolong and/or intensify sexual experience, mainly by some communities of men who have sex with men (MSM). Four substances are typically associated with chemsex: methamphetamine, mephedrone, GHB/GBL, and ketamine. While there is a lot of evidence for increased prevalence of HIV, sexually transmitted infections and other sexual health measures among MSM, who engage in chemsex, there has been little research on mental health aspects. This study aims to describe aspects of mental health among a sample of German men who have sex with men (MSM) who engage in chemsex and to describe potentially adverse consequences of chemsex behavior. Method: This paper refers to a subset of participants from the German Chemsex Survey, an MSM-community recruited, self-completed online survey with a self-selected convenience sample. The survey comprised 420 different items considering recreational substance use, substance use in sexual settings, mental health, sexual transmitted infections, adverse consequences of chemsex behavior, and experiences of non-consensual sex acts. A group of participants who practiced chemsex in the last 12 months (n=280) was compared to men who did not use substances in a sexual context (n=177). Logistical regression was utilized to determine whether mental health measures can predict adverse consequences of engagement in chemsex behaviors. Results: A total of 1583 men started the survey; 1050 participants provided information on substance use. Twenty-seven percent of participants (n=280) reported that they used methamphetamine, mephedrone, GHB/GBL and/or ketamine in a sexual setting in the last 12 months. The chemsex group showed significantly higher mean scores for depression, anxiety, and somatization than the non-chemsex group. The chemsex group reported significantly higher incidences of non-consensual sex acts compared with the non-chemsex group. Some men in the chemsex-group experienced potentially adverse consequences. Discussion: Mean scores for depression, anxiety, and somatization were significantly higher in the chemsex-group, but effect sizes were low. Both groups reported poorer mental health compared to men in the German general population. Mental health measures did not contribute to predict potentially adverse consequences of chemsex behavior.